(untitled) (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: The main purpose of this paper is to understand the current situation of walking power, analyze the basic technology of walking power, and put forward the idea of creating walking power. Throughout the development of ancient health preserving methods, lying, sitting and standing are the main forms; In modern times, several health preserving methods widely known by the public, such as Baduanjin, Wuqinxi, Yijinjing, etc., are mainly vertical methods. Although there are Xingshi Gongfa, it is less popular and less content. But as one of the basic needs of human beings, walking is also an important part of Chinese traditional health preserving methods, which needs further understanding and research. Therefore, this paper takes Xingbu Gong as the breakthrough point, analyzes the technical composition of Xingbu Gong, and puts forward the creative ideas of Xingbu Gong, so as to provide a reference for the development of Xingbu Gong. Methods: The main research methods used in this paper are literature review, induction and deduction. The literature method is mainly through CNKI and the library of Shanghai Institute of physical education to collect the existing papers, works and academic reports related to xingbugong, and to sort out and analyze the literature related to xingbugong. Induction and deduction method is mainly through the further collation and analysis of the data of walking power, comparing the similarities and differences of existing and different walking power, extracting the basic technical components of walking power, and analyzing the basic technical components. After understanding the basic components of Xingbu Gong, this paper designs a creative idea of Xingbu Gong combined with the existing traditional health preserving methods and its own characteristics. Results: The results of this paper are divided into the following three parts. The first part is the main content of the existing walk-through work. At present, most of the walking work exists in the comprehensive health work books. Such as "static Qigong - practical Qigong series" in addition to the traditional walking, but also with running and swimming skills. The rest of the health work books cover the walking work is also: "practical Qigong manual" natural breathing slow-step action, wind breathing method fast-step action; "Qigong Selected Sequel" reflective movement step-by-step practice, walking one, walking two, walking three, Su Dongpo fitness practice-practice; "Chinese four-word body-supporting work" walking deep breathing method, walking spitting method, walking meditation method, cycling quiet method; "Rehabilitation Qigong Selection" step back to work; Qigong self-control rapid therapy for rapid treatment of the disease; Qigong Fitness Law lists eight different walking steps; "Chinese Qigong Selection" running work; The Guide to The Practice of 100 Diseases - The Practice of Body Work lists five different walking steps; "Chinese Medical Qigong" and so on. In Qigong books, there are two sets of Xingbu Gongfa, which appear more frequently: Qigong for regulating breath and Qigong for supplementing qi, and Qigong for moving and transforming Qi. Qigong is mainly composed of three parts: rising, moving and closing. There are two ways to raise the momentum, namely, three Shuxi in Dantian or blowing breath in fixed steps; Xinggong is a positive part, which consists of six parts: regulating body, regulating kidney, regulating lung, regulating liver, regulating spleen and regulating heart; The closing part corresponds to the positive work part, and different positive work has different closing ways. Qiaobu movement and transformation work is also composed of three sections: rising power, moving power and closing power. There is one main way of rising power, which is three Dan opening and closing style, also known as three Tian opening and closing style and three Tian opening and closing method; The walking part is called "walking slowly" method, which consists of one action and is repeated; There are four kinds of closing part, such as opening and closing of Ertian, kneading abdomen, three shying and breathing, and standing in a relaxed and quiet state. The second part is the basic technology of walking power. It is mainly divided into gesture, landing method, footwork, walking route and breathing method. Gestures include palm, grip and hook; Landing methods are divided into forefoot landing, heel landing, lateral foot landing, medial foot landing, full foot landing, and foot swing button landing; The footwork is divided into stride, cross step, high bow step, t-step, high leg raising step and leg bending step; Walking routes include forward route, backward route, turn back route, 8-line, mouth line, circular route and broken line route; Breathing methods include heel breathing, natural breathing and abdominal breathing. The third part is the creative ideas of xingbugong. Xingbugong continues to adhere to the principle of fitness Qigong, and puts forward the following creative perspectives. First, from the perspective of the combination of various sports forms and health preserving methods. Nowadays, there are various forms of movement, so Xingbu Gong is also combined with the current form of movement. In addition to the traditional walking method of jogging and fast walking, its form of exercise can also be combined with jogging and cycling to form a new walking method. Second, from the perspective of prescription creation. Xingbugong prescription can be divided into prevention and treatment of certain diseases and rehabilitation of certain diseases. The creation and composition of the whole content is based on a certain disease. Third, from the perspective of distance of movement. The movement distance can be divided into original position, short distance and long distance. According to the movement distance, it can be divided into original position walking work, short distance walking work and long distance walking work. Fourth, from the perspective of the length of exercise time. Exercise time can be divided into single exercise duration and exercise season. At present, the single time length of walking is mainly 20-30 minutes. At the same time, walking is divided into summer practice and winter practice. However, considering the factors such as the length of time, seasonal changes and so on, from the perspective of exercise time, Xinggong can be divided into 20-30 minutes of short-term exercise, about 1 hour of medium-term exercise and 1. 5 hours or more of long-term exercise; At the same time, it can be divided into four seasons. Conclusion: Therefore, the research conclusion of this paper is that the proportion of the existing walking exercises in the total number of health preserving exercises is relatively small, and most of the walking exercises are mainly single action, on this basis, combined with guidance and breathing regulation; Based on a large number of data, this paper analyzes the basic technical components of walking skill, including gesture, landing method, footwork, walking route and breathing method; Based on the basic technical movements of walking and the existing data of walking, this paper puts forward four main creative perspectives: the combination of various forms of movement, the combination of prescriptions, the distance of movement and the length of movement time.